Deviation of Phase Boundary Conditions for Hydrates of Small-Chain Hydrocarbons (CH4, C2H6 and C3H8) When Formed Within Porous Sediments - Alberto Maria Gambelli (Energies)
This research deals with gas hydrates formation and dissociation within a marine quartz-based porous sediment and in batch conditions. Hydrates were formed with small-chain hydrocarbons included in natural gas mixtures: methane and also ethane and propane. The dissociation values were collected and provided both graphically and numerically. The results were then compared with the theoretical hydrate-liquid-vapor phase boundary equilibrium for the same species, defined according to the existing literature. The deviation of the experimental results from the ideal ones, associated with the porous sediment, was quantified and discussed. For the scope, the grain size distribution and chemical composition of the sediment were provided along with the text. The results proved that the different size of guest species and, consequently, the different hydrate structures formed, played a relevant role in determining the promoting, inhibiting or neutral behavior of the porous sediment during the process.